Are health professionals serious about breast self-examination? a study from a medical college and tertiary level hospital of Central India - Kawalkar, Aishwarya Narendra; Koparkar, Anil Ramesh (International Journal of Research in Medical Sciences, 2017)
Background: Breast cancer is increasing in prevalence all over the world and health professionals are having main responsibility to counter this rapid increase by early diagnosis and prompt treatment. Breast self-examination is cheapest, easy and most cost-effective way of screening of breast cancer. If health professionals themselves know, understand and practice BSE, then only they are expected to be oriented towards taking this tool seriously and include in their practice. Therefore, to study breast self-examination (BSE) among Health professionals in tertiary hospital this study was conducted. Methods: This cross-sectional study was conducted at a medical college and tertiary level hospital in Nagpur, from August 2016 to October 2016. All female Interns, female Post-graduate students, all female teaching staff in all clinical, para-clinical and non-clinical departments and nurses were included in the study. Total 400 Health professionals had participated in this study. Data entry and analysis was done using EPI-Info. Results: In this study, 93.75% of participants were having knowledge regarding BSE but only 86.36% practically knew how to do BSE. Moreover only 74.75% were practicing BSE (at least once in a month). Common reasons for not practicing BSE were ‘not having time’, ‘don’t feel it’s necessary’ and ‘feels awkward’. Conclusions: This study revealed that there is strong need of intervention in health professionals in making them aware of BSE, to improve knowledge and making BSE a universal practice them.